Symposium 6: A Theoretical Design for Learning Model addressing the Networked Society - Nielsen, Janni; Levinsen, Karin; Sørensen, Birgitte Holm (Proceedings of the International Conference on Networked Learning, 2010)
The transition from the industrial to the networked society produces contradictions that challenge the educational system and force it to adapt to new conditions. In a Danish virtual Master in Information and Communication Technologies and Learning (MIL) these contradictions appear as a field of tension between time resources and the demand for educational quality. The size of curriculum is growing while the time available for learning is continuously decreasing. We teach for deep learning but are confronted by students’ cost-benefit strategies when they navigate through the study programme under time pressure. To meet these challenges a Design for Learning Model has been developed. The aim is to provide a scaffold that ensures students´ acquisition of the subject matter within a time limit and at a learning quality that support their deep learning process during a subsequent period of on-line study work. In the process of moving from theory to application our model passes through three stages: 1) Conceptual modelling; 2) Orchestration, and 3) Operationalization that direct the students’ performance in practice when the design model is applied. Moving from conceptual modelling and orchestration to operationalization is a move from the generic theoretical modelling into a specific description of an application of the model in a specific context. We discuss our theoretical Design for Learning Model arguing that the model gives birth to scaffolding which enables students to maintain progression in the learning process and develop Networked Society competencies.